2017
DOI: 10.1038/s41598-017-16308-2
|View full text |Cite
|
Sign up to set email alerts
|

Repair of the TGFBI gene in human corneal keratocytes derived from a granular corneal dystrophy patient via CRISPR/Cas9-induced homology-directed repair

Abstract: Granular corneal dystrophy (GCD) is an autosomal dominant hereditary disease in which multiple discrete and irregularly shaped granular opacities are deposited in the corneal stroma. GCD is caused by a point mutation in the transforming growth factor-β-induced (TGFBI) gene, located on chromosome 5q31. Here, we report the first successful application of CRISPR-Cas9-mediated genome editing for the correction of a TGFBI mutation in GCD patient-derived primary corneal keratocytes via homology-directed repair (HDR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…Recently, gene therapy has developed new insights into the treatment of several genetic diseases [36]. In vitro , decreasing mutant TGFBIp expression with an allele-specific nature siRNA and correcting mutant DNA in TGFBI -mutant cells with site-specific genome editing technologies seem to provide promising approaches for TGFBI -linked CDs [37, 38].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, gene therapy has developed new insights into the treatment of several genetic diseases [36]. In vitro , decreasing mutant TGFBIp expression with an allele-specific nature siRNA and correcting mutant DNA in TGFBI -mutant cells with site-specific genome editing technologies seem to provide promising approaches for TGFBI -linked CDs [37, 38].…”
Section: Discussionmentioning
confidence: 99%
“… 32 reported that the macroscopic, microscopic, and ultrastructural appearance of TGFBI -null mouse cornea remain unaffected, suggesting that partial or complete knockdown of TGFBI could be a potential therapy against TGFBI -linked corneal dystrophies. Currently, correction of p.(Arg124His) mutation in cornea by knocking out the mutated allele is being attempted for the treatment of GCD2 33 , 34 . Our present data indicate that the knockout of the allele should be very precise during gene therapy, in case of the heterozygote, such that only the allele containing p.(Arg124His) mutation is treated, leaving the normal-sequence allele intact.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, CRISPR-Cas9-mediated genome editing for the correction of a TGFBI mutation in GCD patient-derived primary corneal keratocytes was reported [7]. Gene therapy for heredity corneal diseases may be possible in the future, it is important to accurately assess renal symptoms.…”
Section: Discussionmentioning
confidence: 99%